The Civil War memoirs of a Virginia cavalryman - Hubard, Robert Thruston, 1839-1921 (University of Alabama Press, 2007)
A witness who brings remarkable life and color to the Civil War in the East. Robert Hubard was an enlisted man and officer of the 3rd Virginia Cavalry in the Army of Northern Virginia (CSA) from 1861 through 1865. He wrote his memoir during an extended convalescence spent at his father's Virginia plantation after being wounded at the battle of Five Forks on April 1, 1865. Hubard served under such Confederate luminaries as Jeb Stuart, Fitz Lee, Wade Hampton, and Thomas L. Rosser. He and his unit fought at the battles of Antietam, on the Chambersburg Raid, in the Shenandoah Valley, at Fredericksburg, Kelly's Ford, Chancellorsville, Gettysburg, Bristoe Station, and down into Virginia from the Wilderness to nearly the end of the war at Five Forks.